1965
DOI: 10.1071/ea9650166
|View full text |Cite
|
Sign up to set email alerts
|

Air dispersal of conidia of Monilinia fructicola in peach orchards

Abstract: Air dispersal was found to be an important means of disseminating conidia of Monilinia fructicola. In the Murrumbidgee Irrigation Areas of New South Wales only one major dispersal period occurred in each of the four years of this study. This period commenced about one month before peach harvest and continued for about two months after harvest. Greatest numbers of conidia were trapped in seasons when rain fell about harvest time. Conidial concentrations were related to the number of fruit infections present. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 7 publications
2
17
0
2
Order By: Relevance
“…1 and 2). Previous studies on M. fructicola demonstrated that late spring and early summer dispersal of conidia originated from mummified fruit, blighted blossoms and spurs (Corbin et al 1968;Kable 1965). However, M. fructigena does not cause blossom and/or twig blight in apple in the Central-European region (Holb 2004) and most overwintered mummified fruit are destroyed or not able to sporulate any longer by the occurrence of first (Xu et al 2001b;Van Leeuwen et al 2002b).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…1 and 2). Previous studies on M. fructicola demonstrated that late spring and early summer dispersal of conidia originated from mummified fruit, blighted blossoms and spurs (Corbin et al 1968;Kable 1965). However, M. fructigena does not cause blossom and/or twig blight in apple in the Central-European region (Holb 2004) and most overwintered mummified fruit are destroyed or not able to sporulate any longer by the occurrence of first (Xu et al 2001b;Van Leeuwen et al 2002b).…”
Section: Discussionmentioning
confidence: 93%
“…The spore trap inlet orifices were about 1.5 m above ground level as was suggested by previous studies on Monilinia spp. (Kable 1965;Corbin et al 1968;Van Leeuwen 2000). Spore traps were operated from 20 May until mid-October in each year.…”
Section: Quantifying Airborne Conidiamentioning
confidence: 94%
“…The results show that ascospore dispersal of S. fructicola falls into Hirst's daytime dry-airspora grouping, the same as for the conidial phase of S. fructicola or S. laxa (Kable 1964;Jenkins 1965;Corbin et al 1968;Corbin & Ogawa 1974). Although rain and dew periods were frequent during the 27-day period of trapping, in few cases did ascospore peaks coincide with them.…”
Section: Discussionmentioning
confidence: 91%
“…Conidial levels in the orchard atmosphere have been studied (Bucksteeg 1939;Wilson & Baker 1946;Kable 1964;Jenkins 1965;Corbin et af. 1968;Corbin & Ogawa 1974), but apart from observations on apothecial development and ascospore release (Norton 1902;Roberts & Dunegan 1932;Harrison 1935), no one has studied daily ascospore fluctuations during blossom, possibly because in other regions ascospores are not thought to be as important as conidia for primary (blossom) infection (Wade 1955;Millikan 1958).…”
Section: Introducfionmentioning
confidence: 99%
“…conidia can be dispersed in the air, in the 1. INTRODUCTION 25 rain, or by some insects (Kable, 1965;Luo et al, 2001b). There is a positive correlation between the number of conidia of Monilinia spp.…”
Section: Introduction 21mentioning
confidence: 99%